Getting on the job ladder: The policy drivers of hiring transitions - Causa, Orsetta (OECD Publishing, 2022)
This paper delivers new evidence for European countries on the role of a wide range of policies for workers' mobility in terms of hiring transitions into jobs, with an emphasis on differences across socio-economic groups. Labour market transitions are relevant in the current context where the ongoing recovery from the COVID-19 crisis is characterised by labour shortages and at the same time still low employment in a number of countries. The analysis focuses on the probability to transition from unemployment and selected forms of inactivity (e.g. fulfilling domestic tasks, studying) to jobs and from one job to another. Results of this work show the strong association between hiring flows and the business cycle with specific patterns during recoveries, recessions and expansions. The analysis further reveals that a broad range of policies influence hiring transitions, such as labour market policies, taxes and social support programmes but also product market regulations and regulations affecting certain professions. Country-specific priorities will vary depending on context, challenges and social preferences. Yet common policy objectives at the current recovery context are likely to improve the job prospects of the non-employed, especially youth, low-skilled and women, to help the recovery, foster reallocation and to address labour shortages
Keywords: Economics